MULTI-TEMPORAL ANALYSIS OF LAND USE AND OCCUPATION IN THE RIACHO SERTÃOZINHO WATERSHED, PARAÍBA, BRAZIL: SUBSIDY FOR ENVIRONMENTAL PLANNING (Environmental Smoke, 2020)
In the vicinity of the Sertãozinho stream microbasin, the expansion of irregular urban occupations and numerous land uses along the drainage are notorious. The watershed studied is characterized by an intermittent river and fits as a Permanent Preservation Area (PPA). The objective of the present study is to carry out a diagnosis of the use and occupation in the Permanent Preservation Area in the Sertãozinho stream microbasin, municipality of Mamanguape-PB. The delimitation of the watershed was carried out and photointerpretation techniques were used with Google Earth Pro images to identify the space-time dynamics and the historical process of land use and occupation in the APP. With the surveys carried out, it was possible to verify that there was irregular occupation and consequent degradation in the APPs and around the creek. However, it is noted that the main problems found in the Sertãozinho stream microbasin are a reflection of the irregular use and occupation of the land, and the Plan for the Recovery of Degraded Areas-PRAD is important for the recovery of the local ecological balance.